Сучасна українська та польська історіографії про волинську трагедію 1943 року - Мищак, І. (Інститут історії України НАН України, 2008)
У статті розглянуто інтерпретацію істориками двох держав українсько–польського збройного конфлікту на Волині в роки Другої світової війни. Подано основні розбіжності в поглядах на причини трагедії. Водночас зазначається, що твердження ряду фахівців про „українське” і „польське” бачення причин конфлікту не зовсім доречне через наявність в обох країнах різних поглядів щодо причин українсько–польського протистояння. In the paper there are given consideration to interpretation of the Ukrainian-Polish armed conflict on Volyn within the ІІ World War by the historians of two countries. The basic divergences in views on the reasons of the tragedy are submitted. At the same time it is noted that the statements of some experts about «Ukrainian» and «Polish» visions of reasons of the conflict are not absolutely pertinent because of the presence in both countries different views concerning the reasons of the Ukrainian-Polish confronting.